ACC Inhibition by Lanatoside C: A Repurposed MASH Therapy - Bai, Xianxiang; Duan, Rubin; Xiao, Bin (Combinatorial Chemistry & High Throughput Screening, 2026)
<span class=
Keywords: lipid metabolism regulation